Analysis of Instagram use Cultivates a Show-Off Culture Trend that Contributes to Mental Disorders - Kho, Gerson Ralph Manuel; Rachmad, Teguh Hidayatul; Sasongko, Yohanes Probo Dwi (Jurnal The Messenger, 2025)
Purpose: This study aims to deepen the understanding of mental health issues prevalent in society, particularly among higher education students, resulting from the show-off culture on social media. Technological advancements, especially on highly visual platforms like Instagram, have reshaped how students perceive and experience mental well-being.   Methods: Employing a qualitative descriptive approach, this research analyzes the lived experiences of two college students in North Jakarta, Gladys and Viola. The use of social media, particularly Instagram, has become an integral part of adolescents' daily lives, as reflected in the experiences of Gladys and Viola, who have both used Instagram for over five years. Data were collected through in-depth interviews structured with theoretical frameworks related to mental health to understand their psychological responses to social media interactions.   Findings: The interviews revealed that both informants initially derived satisfaction and validation from likes and comments. However, this evolved into a source of significant distress when engagement declined. Both subjects experienced symptoms of anxiety, inferiority, and social withdrawal due to upward social comparison and the pressure to maintain a curated online persona. The study found that their recovery required professional psychological intervention and a conscious restriction of social media usage to regain emotional stability.   Originality: This research contributes to the Social Comparison Theory by providing empirical evidence from the Indonesian context, specifically highlighting how the aestheticization of life on Instagram accelerates the transition from validation-seeking behavior to diagnosed mental health disorders among youth, underscoring the urgency for digital literacy and authentic content creation.